Choir Singing Practice and Temporal Ordering in the Elderly - Zukowski, Debora Bonizio; Junker, David Bretanha; da Silva, Isabella Monteiro Castro; Viana, Lucas Moura; de Oliveira, Carlos Augusto Pires (International Archives of Otorhinolaryngology, 2021)
Introduction The importance of temporal ordering and sequencing in the auditory system is discussed because these are considered basic functions for language.Objective To verify the correlation between the practice of choir music and the temporal ordering in elderly with no prior formal musical experience.Method The study design is cross-sectional. The sample consisted of 85 elderly individuals of both genders, ≥ 60 years old, and it was composed of 43 elderly individuals with no prior formal musical experience but choir participation (research group) and 42 elderly individuals who never sang in a choir and had no music training during their life (control group). The research group was divided based on three categories of choir time. The performances of the research and control groups were compared with pitch pattern sequence (PPS), verbal condition (PPSverb), humming condition (PPShum), and duration pattern sequence (DPS) tests.Results The mean PPShum and PPSverb showed a statistically significant difference by choir time with a different mean of PPShum between the no singing experience group (59%) and the > 10 years of singing experience group (90%) (p = 0.02). Regarding the averages of PPSverb, there was a statistically significant difference between the no singing experience (23%) and > 10 years of choir time (54%) (p = 0.02) groups.Conclusion The findings indicate a better performance in the temporal ordering of the elderly who are not formal musicians but who have choir experience in the research group in relation to those with no choir experience in the control group.
Keywords: auditory perception; hearing tests; singing; aging